Investigation of the tribological properties of POM and UHMWPE radial journal bearings made with different surface quality - Artun, Yakup; Azeloglu, C. Oktay; Taylan, Gokhan (SAGE PUBLICATIONS LTD, 2024)
Journal bearings are essential machine elements that are widely used in the bearing of rotating or oscillating machine parts. Many studies in the literature examine the tribological properties of journal bearings. Most of these studies focus on polymer journal bearings and testing the tribological performances of different bearing materials with the same surface quality. In this article, radial journal bearings produced from ultra-high molecular weight polyethylene (UHMWPE) material and polyoxymethylene (POM) material in two different surface qualities in the range of N7-N8 and N10-N11 were tested under different load and different speed scenarios and their tribological performances and relationship of this performance between material and surface roughness were investigated. For this purpose, first of all, bearing samples were designed and manufactured. All samples' tribological and physical properties before the tests were measured, and then tests were carried out according to the determined scenarios. Different loads, different speeds, and different sliding distances were used in the scenarios. As a result, 96 tests were carried out by testing each situation three times in eight scenarios, with two different surface qualities from two different materials. In the tests, the friction coefficient, temperature, and weight loss values of all samples were measured, and after the tests, surface roughness measurements and SEM analyses were made. As a result, all the data obtained from the tests and measuring devices were compared with the pre-test conditions and material and surface quality. The results obtained from the comparisons and the evaluations of tribological performance are discussed in the conclusion part. The study results show that the material and the surface quality significantly affect the tribological performance.
Keywords: journal bearings; UHMWPE; POM; different surface quality; tribological performance; DRY FRICTION; BEHAVIORS; PTFE; WEAR; Engineering